2021
DOI: 10.3389/fimmu.2021.736638
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Sex Differences at Disease Manifestation in ANCA-Associated Glomerulonephritis

Abstract: Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a small vessel vasculitis affecting multiple organ systems, including the kidney. Besides investigations focusing on renal outcomes, sex differences associated with distinct clinical and histopathological findings in ANCA glomerulonephritis (GN) have not been systematically investigated. Therefore, we here aimed to systematically analyze sex differences in patients with AAV and biopsy-proven ANCA GN. We provide a comprehensive analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…83,84 There are limited data exploring differences between the sexes with respect to clinical presentations of AAV. Tampe et al 85 found no sex-specific associations between clinical characteristics or with serum or urinary parameters. They also reported that systemic disease activity does not differ between the sexes.…”
Section: Aavmentioning
confidence: 96%
“…83,84 There are limited data exploring differences between the sexes with respect to clinical presentations of AAV. Tampe et al 85 found no sex-specific associations between clinical characteristics or with serum or urinary parameters. They also reported that systemic disease activity does not differ between the sexes.…”
Section: Aavmentioning
confidence: 96%
“…A cohort of 53 kidney-biopsy-confirmed cases of ANCA-associated renal vasculitis was retrospectively enrolled between 2015 and 2020 in a single-center observational study at the University Medical Center Göttingen, Göttingen, Germany [ 51 , 52 , 53 , 54 , 55 ]. In addition, a total of 138 disease controls—including AL amyloidosis, tubulointerstitial nephritis, diabetic kidney disease, focal segmental glomerulosclerosis (FSGS), immunoglobulin A (IgA) nephropathy, IgA vasculitis, hypertensive nephropathy, lupus nephritis, membranous nephropathy, minimal change disease, monoclonal dense deposit disease (DDD), post-infectious glomerulonephritis (GN), and thrombotic microangiopathy—were also evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…A total number of 53 cases admitted the University Medical Center Göttingen with confirmed ANCA-associated renal vasculitis retrospectively included between 2015 till 2020, the patient cohort has in part previously been described 23 27 . None of the patients required mechanical ventilation due to respiratory failure, and 1 patient was ventilated due to status epilepticus.…”
Section: Methodsmentioning
confidence: 99%
“…Particularly, data on critical illness during the initial course of disease are scarce and remains poorly determined. Therefore, the purpose of this retrospective study was to identify predictors of critical illness in a previously described cohort of patients with biopsy-proven ANCA-associated renal vasculitis 23 27 .…”
Section: Introductionmentioning
confidence: 99%